(untitled) - Thomas R Cole (Cambridge, New York, 1997)
The book is both a cultural history of aging and a contribution to public dialogues about the meaning and significance of later life. It reflects a continuing ambiguity and multiplicity of attitudes in society at every stage
Keywords: middle class - america - history,middle class - french - history